Modelagem espacial das fragilidades neotect?nicas na Costa do Descobrimento, Sul do Estado da Bahia - Rojas Gonz?lez, Oriana Isabel (2019)
This work aims to model tectonic fragilities zones present in the Discovery Coast, southern Bahia State, where Neogene sediments of the Barreiras Formation outcrops. The study area is dominated by tablelands that reach the coast, originating sea cliffs up to 40 m high. Field studies were developed in order to observe, describe, measure and interpret geological structures, especially joints and faults that indicate the action of neotectonics in the studied area. From the MDT/SRTM data, processed through Geographic Information Systems (GIS) using ArcMap, a set of thematic maps was made, highlighting the structural indices (lineament map, lineament density and lineament frequency), geomorphological indices (drainage density, flow frequency and topographic humidity index) and morphotectonic indices (relief amplitude and slope gradient). In addition, it was applied the weighted linear combination technique (WLC), identifying areas that would keep records of the most recent tectonic action. Field data and image analysis demonstrated a higher density of lineaments in the NW-SE and secondarily in the NE-SW direction totaling 908 and 722 respectively. The map tectonic fragilities highlight higher levels of the most recent deformations in the Camurugi, Trancoso and Cara?va sub-basins, evidenced by the tilting and modification of drainage patterns. The integration of the maps highlighting the structural, geomorphological and morphotectonic indices, proved to be an effective method for making the tectonic fragility map, confirming the neotectonics action in the Discovery Coast and opening possibilities for further studies to develop along the east coast of Brazil.